Commercial yet social: The practices and logics of bringing mini-grid electricity to rural villages in Kenya. (October 2020) - Pedersen, Mathilde Brix; Wehrmeyer, Walter; Nygaard, Ivan
Abstract: Private mini-grid developers, which deliver power to rural communities in developing countries through for-profit business models, represent an alternative organisational model compared to traditional state-led, donor-led or community-driven models of rural electrification. However, as the 'private model' covers many different ways of doing business, this paper seeks to broaden our understanding of its complexities. This is done by using insights into organisational hybridity as a defining characteristic of organisations that have a dual mission consisting of social and economic aims and by applying the analytical concept of institutional logics. The paper explores how four different mini-grid firms in Kenya draw on both a commercial logic and a social welfare logic in their everyday operational activities in order to achieve their goals. By studying the practices, activities and sense-making of the four firms, as well as the effects of these practices in the targeted areas, the paper illustrates how some firms prioritise one logic over the other, while other firms blend the two logics in their work. The paper finds that firms using a blending approach seem to derive synergies from integrating the two logics into their work. However, more research is needed to improve understanding of this link and of the organisational drivers that underpin each approach.